Pembuatan Butir Soal SD berbasis HOTS ( High Order Thinking Skills) untuk Menilai Kompetensi Siswa dalam Kurikulum 2013 - Slamet Widodo; Adhy Putri Rilianti; Atika Maulidina Hs (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
Currently, teachers must have the skills to create HOTS-based questions because the government, through the revised edition of the 2013 curriculum policy, states that the taxonomy of thinking is taught at all levels of education. The aim of creating HOTS-based questions is to prepare students to have logical, critical and creative thinking qualifications that are able to foster reasoning processes based on the complexity of dynamic changes in society. The process of creating HOTS-based questions is: 1) determining the goal of the questions to be achieved by students, which consists of: a) the ability to search and study information, b) connecting various information relationships, and c) applying information to solve problems, 2) creating questions that are able to develop students' reasoning abilities, which consist of various activities, namely: a) exploring, b) analyzing, c) synthesizing, d) evaluating, e) developing reasoning abilities when obtaining information, and f) critical thinking